Exploring the impact of protein intake on the association between oxidative balance score and lean mass in adults aged 20–59: NHANES 2011–2018 - Jia-qi Hao; Zi-xuan Zhuang; Shu-yue Hu; Yu-jie Zhang; Jia-wan Zhang; Feng-Jun He; Rui Wang; Wen Zhuang; Mo-jin Wang (Journal of Health, Population and Nutrition, 2024)
Abstract Background Previous studies have established a correlation between the pathogenesis of oxidative stress and sarcopenia. The Oxidative Balance Score (OBS) is an integrated measure that reflects the overall balance of antioxidants and pro-oxidants in dietary components and lifestyle. However, there are limited reports on the association between OBS and lean mass and the impact of protein intake on the association between OBS and lean mass. Methods Using data from the National Health and Nutrition Examination Survey from 2011 to 2018, multivariate linear and logistic regression analyses were conducted to explore the associations between OBS and outcomes. The findings were then illustrated through fitted smoothing curves and threshold effect analyses. Results This study included 2,441 participants, demonstrating that higher OBS is significantly associated with an increased ratio of appendicular lean mass to body mass index. Key inflection points at OBS 31 mark pronounced changes in these associations, with age and protein intake notably affecting the association. The effect of OBS on lean mass varies among populations with high and low protein intake. Conclusions Our findings suggest that OBS is significantly and positively associated with lean mass. A high protein intake of more than 84.5 g/day may enhance the role of OBS in influencing muscle health to improve muscle outcomes.